The Career adaptability among Young Adulthood : A Systematic Literature Review - Rasyidi, Syifa Nurul Ain; Akhmad, Sudaryat Nurdin; Sudrajat, Dadang; Nadhirah, Nadia Aulia (ProGCouns: Journal of Professionals in Guidance and Counseling, 2021)
The success of a person completing typical developmental tasks at certain stages of development lies in career adaptability. Career adaptability is an individual's readiness for a career in accordance with the effort to complete career-related developmental tasks. To suggest future development directions, this article systematically reviews the review literature on future adaptations. This article uses a systematic literature review (SLR) approach. This article uses 47 articles from 17 journals with research that has been conducted in various Asian countries, Europe, South America and other countries such as South Africa, China, Korea and Australia as the source. This article concludes that the adaptability possessed in adulthood is included in the high or mature category. Where it focuses more on aspects that are owned by the career and adult reasons why the adaptation at that time is high and the advantages that are owned when having the abilities possessed by a high or mature career. This article concludes with some suggestions for further research that could be produced in the future.